Community wildfire protection planning in the American West: homogeneity within diversity?. Issue 3 (3rd March 2016) - Abrams, Jesse; Nielsen-Pincus, Max; Paveglio, Travis; Moseley, Cassandra
Abstract : As large wildfires have become common across the American West, federal policies such as the Healthy Forests Restoration Act have empowered local communities to plan for their own wildfire protection. Here, we present an analysis of 113 community wildfire protection plans from 10 western states where large fires have recently occurred. These plans contain wide diversity in terms of specific plan elements and dimensions, yet less diversity in the paradigms underlying their fire protection approaches. These patterns held true across both plans constructed solely by local actors as well as those constructed with the help of outside consultant expertise.